Awareness of High Blood Pressure Stimulates Platelet Release Reaction - Rostrup, Morten; Mundal, Håvard Holth; Kjeldsen, Sverre Erik; Gjesdal, Knut; Eide, Ivar (Thrombosis and Haemostasis, 1990)
The present study aimed at testing the hypothesis of a link between mental stress and blood platelet function. Twenty-nine 19-year-old men were recruited from the 98th percentile of mean blood pressure (116 mmHg) at a routine medical screening. They were not informed about their elevated blood pressures at the time of the screening. One year later they were randomized into two groups. Group 1 (n = 16) was exposed to mental stress by a letter informing them about their high blood pressure, while group 2 (n = 13) was sent a neutral letter. At an examination 2 weeks later, heart rate (p <0.05) and plasma adrenaline (p <0.05) responses to a cold pressor test were exaggerated in the informed group. The plasma beta-thromoglobulin (pTG) concentration was elevated in the informed group (p <0.05) as was mean blood pressure (p <0.05). (3TG correlated positively with hematocrit (r = 0.59, p <0.005) and mean blood pressure (r = 0.43, p <0.05), and negatively with plasma HDL (r = −0.61, p = 0.001). The study shows that awareness of hypertension induces a hyperadrenergic state which is associated with the platelet release reaction. Under these circumstances platelet release seems to be correlated to established coronary heart disease risk factors.